Efektivitas Pertanian Perkotaan (Urban Farming) dalam Mitigasi Urban Heat Island di Kawasan Perkotaan - Christian Nindyaputra Octarino (ATRIUM: Jurnal Arsitektur, 2022)
Title: The Effectiveness of Urban Farming for Urban Heat Island Mitigation in Urban Areas   Urban farming and greenery are the emerging idea in maintaining a sustainable environment in term of economic, social, and environmental aspects. The existence of urban farming is primarily aimed to maintaining food security for the community, especially in the pandemic crisis. Moreover, the high rate of urbanization also affects the transformation of urban space, which is one of the factors causing climate change. The integration of vegetation in urban area is considered to be a strategy to maintain the quality of the microclimate and reducing the intensity of the urban heat island. This study aims to observe the effectiveness of urban farming/greenery in maintaining the microclimate quality at District of Tompeyan Yogyakarta, which is well known for their urban farming integrated inside the residential areas. Using field measurement and simulation methods, the results show that the vegetation in the outdoor space have a significant impact, especially related to surface temperature and air temperature. The simulation using ENVI-MET shows that there is an increase in the thermal comfort index in the areas with vegetation, although it has not yet reached the ideal value. This represents how the role of vegetation in urban heat island mitigation to provide a comfortable and sustainable environment. The study can be further developed regarding the impact of other physical elements on microclimate to be the foundation for spatial planning recommendations.